2006
DOI: 10.3727/108354206778001503
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cruise-ship Tourism And Stay-over Tourism: A Case Study of the Shift In the Cayman Islands' Tourism Strategy

Abstract: Like all Caribbean destinations, the Cayman Islands has two sectors of tourism: stay-over tourism and cruise-ship tourism. Before the 1990s, the official Cayman Islands' tourism strategy placed more emphasis on the stay-over sector. After the significant drop in the number of stay-over visitors in the late 1990s, the official stance shifted, placing more emphasis on the cruise-ship sector with the intent of converting cruise ship visitors into stay-over visitors. This study investigates the simultaneous relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This is notably less than the US$365 million estimated for air arrival expenditure in the same year, despite the markedly lower percentage of air arrivals recorded (see Figure 1)). These numbers concur with the recognition that despite a general assumption that cruise tourism benefits the local economy (Kido and Kido, 2008), often this industry contributes considerably less than tourism based on air arrivals (Patullo, 2004;Shamsub et al, 2006;Seidl et al, 2007 , approximately half of the total estimated reef surface area excludes reefs on the outer edge of the North Lagoon, or fore-reef slope reefs (Figure 2). The geographical boundary selected for this study was based in part on tourism use.…”
Section: Cruise Ship Tourism In Bermudasupporting
confidence: 78%
See 1 more Smart Citation
“…This is notably less than the US$365 million estimated for air arrival expenditure in the same year, despite the markedly lower percentage of air arrivals recorded (see Figure 1)). These numbers concur with the recognition that despite a general assumption that cruise tourism benefits the local economy (Kido and Kido, 2008), often this industry contributes considerably less than tourism based on air arrivals (Patullo, 2004;Shamsub et al, 2006;Seidl et al, 2007 , approximately half of the total estimated reef surface area excludes reefs on the outer edge of the North Lagoon, or fore-reef slope reefs (Figure 2). The geographical boundary selected for this study was based in part on tourism use.…”
Section: Cruise Ship Tourism In Bermudasupporting
confidence: 78%
“…A recent report (August, 2011) (commissioned by the Bermuda Ministry of Transport to assess the ability of Bermuda's shipping channels to accommodate larger cruise ships) is a clear indication of the government's interest to promote the expanding cruise tourism on the island. This changing cruise ship industry, and more specifically that of the cruise lines serving Bermuda, forces a re-evaluation of the island's carrying capacity, a scenario which has been faced by a number of additional Caribbean destinations, such as the Cayman Islands (Shamsub et al, 2006), the Bahamas and Mexico's Yucatan Peninsula (Patullo, 2004). Much of the literature today appreciates the importance of developing tourism 'sustainably'.…”
mentioning
confidence: 99%
“…As compared to the full strategic substitutes case (point A), equilibrium quantities decrease (resp, increase) for stay-over tourism (resp, for cruise tourism). Results obtained by Shamsub et al (2006) are an illustration of the usual assumption by cruise tourism supporters that cruise tourism is a complement to stay-over tourism. We know that a tourist who has stayed in a country does not really want to come back as a cruise ship passenger.…”
Section: A Simple Static Quantity Game With Differentiated Products Omentioning
confidence: 77%
“…For the Cayman Islands, using time-series data for the period 1971-2000, Shamsub et al (2006) have shown that stay-over tourism is a substitute for cruise ship tourism and cruise ship tourism is a complement to stay-over tourism. This unusual conclusion is given by different cross-price effects: γ 1,nt > 0 for the stayover tourism best response and γ 2,nt < 0 for the cruise tourism best response.…”
Section: A Simple Static Quantity Game With Differentiated Products Omentioning
confidence: 99%
See 1 more Smart Citation